Forever Young - Young, Jimmy, 1921-2016 (London Hodder & Stoughton, 2003)
After 30 years as a DJ on BBC Radio 2, Sir Jimmy Young left the BBC at Christmas 2002. It was a controversial departure behind which lies a story he is only now prepared to reveal. This autobiography charts his career from a singer in the 1950s to his position as BBC Radio 2's top presente
Include Color Illustration and Index
Keywords: Radio broadcasters -- Great Britain -- Young, Jimmy, 1921-2016